2018
DOI: 10.1074/jbc.ra117.000152
|View full text |Cite
|
Sign up to set email alerts
|

The NLR family pyrin domain–containing 11 protein contributes to the regulation of inflammatory signaling

Abstract: Mammalian NLR proteins contribute to the regulation and induction of innate and adaptive immunity in mammals although the function of about half of the currently identified NLR proteins remains poorly characterized. Here we analysed the function of the primate-specific NLRP11 gene product. We show that NLRP11 is highly expressed in immune cells, including myeloid cells, B cells and some B cell lymphoma lines. Overexpression of NLRP11 in human cells did not trigger key innate immune signalling pathways includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 28 publications
4
50
1
Order By: Relevance
“…Feriani et al found significant improvement in inflammatory parameters and cardiac function indicators in exhausted rats after aerobic exercise training. In order to control the harmful effects of inflammation on cardiac function, we need to pay more attention to the regulation of inflammatory pathways and strictly control inflammatory pathways and their activators [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Feriani et al found significant improvement in inflammatory parameters and cardiac function indicators in exhausted rats after aerobic exercise training. In order to control the harmful effects of inflammation on cardiac function, we need to pay more attention to the regulation of inflammatory pathways and strictly control inflammatory pathways and their activators [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier characterization studies on NLRP11 reported that NLRP11 does not colocalize with ASC in 293T cells [30]. Furthermore, NLRP11 does not associate with ASC in transiently transfected living HeLa cells [3]. Hence, we assessed the impact of adenosine activation on NLRP11 and ASC protein interaction by coimmunoprecipitation (Figure 3(a)).…”
Section: Adenosine-induced Nlrp11 Interacts With Asc Adaptormentioning
confidence: 94%
“…NLRs are grouped into four structurally similar subfamilies, namely, NLRA, acidic domain containing; NLRB, baculoviral inhibitory repeat (BIR) domain containing; NLRC, caspase activation and recruitment domain (CARD) containing; and NLRP, pyrin domain (PYD) containing, as well as, NLRX, which has no significant homology to the N-terminal domain of any other member of the NLR subfamily [ 2 ]. Although NLRP11 is commonly considered a primate-specific NLR [ 3 ], rabbits, placentals, bats, pigs, and lemurs also express different isoforms of NLRP11 with amino acid sequence identities ranging from 45.6% to 58.6%. Additionally, sequence comparison analysis revealed that human NLRP11 has the closest amino acid sequence identity to NLRP4 of the nonprimate species Tupaia chinensis (36%) and Mus musculus (33.5%).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, NLRC5 can suppress TLR signaling by modulating IKK activation (Cui et al, 2010), though NLRC5 deficiency does not affect this signaling pathway (Kumar et al, 2011b). Finally, the primate specific NLRP11 suppresses TLR-mediated activation of NF-κB by targeting TRAF6 for degradation in myeloid cells and B-cells (Ellwanger et al, 2018;Qin et al, 2017b;Wu et al, 2017). Together, these emerging properties call into question whether the established role for this family in activating proinflammatory responses may in fact represent an exception rather than a rule.…”
Section: Nlrc5mentioning
confidence: 99%